Trends and Differences in MICE Tourism and Event Tourism Research: A Bibliometric Study (2015–2025) - Prasiwi Citra Resmi; Agustia Dzikir Maulani (Jurnal Ragam Pengabdian, 2026)
Research on MICE tourism and event tourism has increased significantly in recent years, yet the thematic boundaries and relationships between these two fields remain unclear in the academic literature. The overlapping use of concepts often leads to ambiguity regarding their respective research orientations. This study addresses this issue by examining trends and thematic differences between MICE tourism and event tourism through a bibliometric approach. Data were collected from the Scopus database, covering publications from 2015 to 2025 that focus on MICE tourism, event tourism, and related topics. A total of 308 documents were analysed using VOS viewer to map publication trends and co-occurrence of author keywords. The analysis focused on identifying dominant themes, thematic clusters, and the structural positions of MICE tourism and event tourism within the research network. The results indicate that both fields are closely connected and develop within the same research landscape, but with different thematic emphases. MICE tourism is more strongly oriented toward business tourism and the meetings industry, while event tourism functions as a connecting theme linking business-related events with broader tourism and destination contexts. The findings demonstrate that the distinction between MICE tourism and event tourism is not dichotomous, but rather reflects differences in thematic orientation and structural roles within the literature. This study contributes to a clearer understanding of the intellectual structure of MICE and event tourism research and provides a comprehensive overview of their development over the past decade.